Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

Find the solution to the system of equations below (you can do this by substitution or elimination).

-4x+y=6
-5x-y=21


Sagot :

Step-by-step explanation:

y=6+4x, as equation (iii)

=> -5x-(6+4x)=21

=> -5x-6-4x=21

=> -5x-4x-6=21

=> -9x-6=21

=> -9x=21+6

=> -9x=27

x= -3, by dividing both sides by -9

So, by inserting x in the first equation,

=> -4(-3)+y=6

=> 12+y=6

=> y=6-12

=> y= -6.

Therefore, x= -3 and y= -6